1962
DOI: 10.1017/s0022172400039322
|View full text |Cite
|
Sign up to set email alerts
|

A note on the immunogenicity of ultra-violet irradiated vaccinia virus in man

Abstract: A preparation of vaccinia virus inactivated by ultra-violet irradiation under strictly controlled conditions, and shown to produce neutralizing antibody and resistance to challenge in rabbits, was active in only about half of 37 human volunteers. It was not, therefore, likely to be usefully immunogenic in man. In the largest single test, 15 of 25 men had unmodified primary skin reactions when challenged with living virus, although five of these had circulating antibody. On the other hand, only three of 10 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Collier, McClean & Vallet (1955) obtained encouraging results in rabbits using ultra-violet-irradiated virus, both in terms of antibody produced and immunity to challenge, but results in a pilot study in man (Kaplan, McClean & Vallet, 1962;Kaplan, 1962;Kaplan et al 1965) were regarded as unsatisfactory, in that the immunity to challenge was not reproduced though antibody was elicited. Amies (1961), RamanaRao (1962) and McNeill (1965) showed formalintreated virus to be immunogenic in rabbits and Herrlich (1959;1964) has used such a vaccine for pre-immunization before vaccination with live virus without, however, completely banishing complications.…”
mentioning
confidence: 99%
“…Collier, McClean & Vallet (1955) obtained encouraging results in rabbits using ultra-violet-irradiated virus, both in terms of antibody produced and immunity to challenge, but results in a pilot study in man (Kaplan, McClean & Vallet, 1962;Kaplan, 1962;Kaplan et al 1965) were regarded as unsatisfactory, in that the immunity to challenge was not reproduced though antibody was elicited. Amies (1961), RamanaRao (1962) and McNeill (1965) showed formalintreated virus to be immunogenic in rabbits and Herrlich (1959;1964) has used such a vaccine for pre-immunization before vaccination with live virus without, however, completely banishing complications.…”
mentioning
confidence: 99%
“…In addition, the efficacy of disinfection may decline sharply as the protein content rises, as has also been described for ultraviolet irradiation. 7 Another factor to consider is that precipitants may clump the particles together reducing random distribution within the specimen, and making identification more problematic.…”
Section: Methods Of Disinfectionmentioning
confidence: 99%
“…In one study using UV-inactivated virus injected subcutaneously (Kaplan et al, 1962), neutralizing antibody titers were observed in only about half of vaccinees (19/37 subjects = 51%), and the low neutralizing activity was often near the limit of detection. Secondary challenge with live vaccinia virus by scarification indicated that only 8/25 (32%) of the subjects vaccinated with UV-inactivated virus showed a modified skin reaction indicative of antiviral immunity.…”
Section: Early Failures Of Inactivated Vaccinesmentioning
confidence: 99%